An in silico approach deciphering the commensal dynamics in the cutaneous milieu - Sumathi Kalankariyan; Anjana Thottapillil; Abha Saxena; Manoj Srivatsn S; Vinitha Kadamkode; Renu Kapoor; Rupak Mitra; Janhavi Raut; KV Venkatesh (npj Systems Biology and Applications)
Abstract The skin microbiota, particularly coagulase-negative staphylococci (CoNS) such as S. epidermidis, plays a crucial role in maintaining skin health and immunity. S. epidermidis, a predominant commensal species, interacts intimately with keratinocytes to regulate immune responses and antimicrobial defence mechanisms. Metabolic byproducts like short-chain fatty acids (SCFAs) influence keratinocyte activation, while cell wall components engage Toll-like receptors (TLRs) to modulate inflammation. These interactions are fundamental for preserving skin homeostasis and combating pathogenic invaders. Our comprehensive mathematical model, integrating commensal dynamics, immune responses, and skin microenvironment variables, provides insights into these intricate interactions. The model delves into the complexities of skin scenarios and perturbations, aiming to understand the colonization dynamics of S. epidermidis and its influence on skin barrier functions. It examines how disruptions in key factors such as AMP, growth factor-mediated repair pathways, and filaggrin mutations influence the behaviour of the system. The study depicts the skin microenvironment as a highly dynamic one, highlighting the critical role of S. epidermidis and capturing its role in barrier dysfunction caused by internal and external factors. By offering insights into skin barrier function and immune responses, the model illuminates key interactions of commensals within the skin microenvironment which can ultimately benefit skin health.